Seismic structural demands taking accuracy of response estimation into account. - Mori, Yasuhiro
Predictors of seismic structural demands (such as inter-storey drift angles) that are less time consuming than nonlinear dynamic analysis (NDA) have proven useful for structural performance assessment and for design. Several techniques have been proposed using the results of a nonlinear static pushover analysis. These techniques often use the maximum response computed via NDA of the inelastic oscillator that is ?equivalent? to the original frame. In practice, it is desirable to estimate the response approximately via a simpler method such as an equivalent linearization technique and uniform hazard spectra at the site. In reliability-based seismic performance assessment and design of a structure, it is necessary to consider the level of accuracy of the techniques used in the assessment. A simple technique is proposed in this paper to estimate the r-year return period value of the inter-storey drift angle of a moment-resisting steel frame using a single uniform hazard spectrum of the r-year return period displacement of an elastic oscillator. The structural demand is estimated using the safety factors evaluated taking the variability in the seismic hazard, accuracy of the techniques for estimating structural response, and the structural performance level into account. The accuracy of the technique is investigated relative to the structural demand estimated more directly from the probability distributions of the seismic hazard.
Keywords: Structural reliability; Steel moment-resisting frame buildings; Inelastic response; Seismic hazard; Random error; Safety factor